IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN TILAWAH AL-QUR’AN DI YAYASAN TAHFIZDUL QUR’AN AL-FAWWAZ MEDAN - Ruslan, Muhammad (Berajah Journal, 2024)
The ability to read the Qur'an according to the rules of tajwid is one of the obligations of a Muslim towards the Qur'an. Unfortunately, many Quranic Education Institutions still implement Quran learning programs in a traditional manner that seems stagnant, especially in the city of Medan. This study aims to analyze the implementation of the Ummi method in Quranic recitation learning at the Tahfidzul Qur'an Foundation Al-Fawwaz in Medan. A qualitative method with a case study approach has been used in this research. The researcher employed in-depth interviews, observations, and document studies to address the research objectives. The study indicates that the implementation of the Ummi method in Quranic recitation learning at the Tahfidzul Qur'an Foundation Al-Fawwaz in Medan is carried out through Quran Teacher Certification with the Ummi Method, Institutional Supervision, Learning Implementation, Periodic Evaluation, and Graduation. Interestingly, based on the findings of this research, a novelty is obtained, namely an interactive communicative Quranic learning model, and classroom management strategies for learners of various ages. This study provides recommendations for future researchers to conduct research in other fields such as management or leadership at the Tahfidzul Qur'an Foundation Al-Fawwaz in Medan.